Secondary consolidation characteristics of organic soil modified by bio-enzyme based on the Gibson model - Zhang, Yixin; Wen, Changping (Frontiers in Materials, 2022)
In order to study the secondary consolidation characteristics of organic soil improved by bioenzyme, the secondary consolidation test was carried out. Firstly, the Gibson rheological model parameters were fitted according to the experimental results. Then, the relationship between rheological model parameters, Ca/Cc value, secondary consolidation coefficient Ca and load were analyzed different ratios of bioenzyme. Finally, the rheological model was used to predict, and the predicted value was in good agreement with the experimental value. The results showed that: (1) The rheological model parameters were negatively correlated with the ratios of bioenzyme and positively correlated with the load value. Some parameters reached the maximum value when the ratio of bioenzyme was 0.01%. (2) The secondary consolidation coefficient was related to the load and showed a certain law. With the increasing of load, the secondary consolidation coefficient Ca finally approached to a stable value. (3) The value of Ca/Cc of improved organic soil varied from 0.042 to 0.1 under various loads.